A guide to reading the encyclical caritas in veritate (2021)
An Encyclical is a "solemn letter addressed by the Supreme Pontiff to all the bishops and faithful of the Catholic world." (Dictionary of the Spanish Language, Twenty-Second Edition) The name of the encyclical depends on the first words with which the document begins. Within the pontificate of Pope Benedict XVI, three encyclicals have been presented.